2010
DOI: 10.1073/pnas.1000601107
|View full text |Cite
|
Sign up to set email alerts
|

Structure of bacterial cellulose synthase subunit D octamer with four inner passageways

Abstract: The cellulose synthesizing terminal complex consisting of subunits A, B, C, and D in Acetobacter xylinum spans the outer and inner cell membranes to synthesize and extrude glucan chains, which are assembled into subelementary fibrils and further into a ribbon. We determined the structures of subunit D (AxCeSD/AxBcsD) with both N- and C-terminal His 6 tags, and in complex with cellopentaose. The structure of AxCeSD shows an exquisite cylinder shape (height: ∼65  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
122
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 47 publications
7
122
0
1
Order By: Relevance
“…The mutated residues may be necessary to organize the individual glucan chains into the composite microfibril and thus promote crystallinity (H-bonding) by facilitating association with other glucan chains. This model is consistent with the only reported crystal structure of a CSC, an octameric structure of the periplasmic AxCeSD subunit in the CSC of the bacterium A. xylinum in complex with a 5-glucose-cellulose product (37). Here, a dimer interface was necessary to facilitate passage and proper alignment of glucan chains into a crystalline microfibril.…”
Section: Discussionsupporting
confidence: 78%
“…The mutated residues may be necessary to organize the individual glucan chains into the composite microfibril and thus promote crystallinity (H-bonding) by facilitating association with other glucan chains. This model is consistent with the only reported crystal structure of a CSC, an octameric structure of the periplasmic AxCeSD subunit in the CSC of the bacterium A. xylinum in complex with a 5-glucose-cellulose product (37). Here, a dimer interface was necessary to facilitate passage and proper alignment of glucan chains into a crystalline microfibril.…”
Section: Discussionsupporting
confidence: 78%
“…Wild-type bcsD is a homolog of acsD of G. xylinus ATCC 53582 (11,23). Cellulose productivity in the N-terminal deletion mutant of bcsD also decreased, although cellulose crystallization produced by the mutant was not investigated (39). These observations suggested that CMCax worked together with BcsD in cellulose crystallization in the wild-type strain.…”
Section: Discussionmentioning
confidence: 73%
“…The structure of BcsD (AxCeSD), a component of the cellulose synthase complex, was found to be a homo-octamer comprised of four dimer subunits with a central pore and cylindrical structure (39). The interfaces between the dimers form four spiral interstices on the wall of the molecular cylinder at a 50°angle from the cylinder (vertical) axis (39).…”
Section: Discussionmentioning
confidence: 99%
“…(Iguchi et al 2000;Shah and Brown 2005;Klemm et al 2006;Hu et al 2008). Nevertheless, the high economic cost of culture media as well as low-yield production limit wide scale industrial production and extended applications of BC (Hu et al 2010;Hong et al 2011). Hence, it is challenging and meaningful to develop new approaches to high-yield BC production at the lowest cost possible.…”
Section: Introductionmentioning
confidence: 99%